An all-oral 6-month regimen for multidrug resistant Tuberculosis: A multicenter randomized controlled clinical trial (the Next Study) - Esmail, Aliasgar; Oelofse, Suzette; Lombard, Carl; Perumal, Rubeshan; Variava, Ebrahim; Martinson, Neil (My University, 2023)
Rationale: Improving treatment outcomes while reducing drug toxicity and shortening the treatment duration to 6 months remains an aspirational goal for the treatment of multi drug resistant /rifampicin-resistant tuberculosis(MDR/RR-TB). Objectives: To conduct a multicenter randomized controlled trial in adults with MDR/RR-TB(i.e., without resistance to fluoroquinolones or aminoglycosides) . Methods: Participants were randomly assigned(1:1ratio)to a 6 month all-oral regimen that included levofloxacin, bed aquiline, and linezolid or the standard-of-care(SOC)>9-month World Health Organization(WHO)-approved injectable-based regimen. The primary endpoint was a favorable WHO-defined treatment outcome (which mandates that prespecified drugs substitution is counted as an unfavorable outcome)24 months after treatment initiation. The trial was stopped prematurely when bed aquiline-based therapy became the standard of care in South Africa. Measurements and Main Results: In total,93 of 111 randomized participants(44 in the comparator arm and 49 in the intervention alarm) were included in the modified intention-to-treatanalysis;51(55%)were HIV coinfected(medianCD4count,158cells/ml).Participants in the intervention arm were 2.2 times more likely to experience a favorable 24-month outcome than participants in the SOC arm(51%[25of49]vs. 22.7%[10of44];riskratio,2.2[1.2–4.1];P=0.006).Toxicity-related drug substitution occurred more frequently in the SOC arm(65.9%[29of44] vs.34.7%[17of49];P=0.001)],82.8%(24of29)owing to kanamycin (mainly hearing loss; replaced by bed aquiline) in the SOC arm, and 64.7% (11of17) owing to fluoroquinolones or aminoglycosides (mainly anemia) in the intervention alarm. Adverse event–related treatment discontinuation in the safety population was more common in the SOC arm(56.4%[31of55]vs.32.1%[17of 56];P=0.007).However, grade 3 adverse events were more common in the intervention alarm(55.4%[31of56]vs.32.7[18of55];P=0.022). Culture conversion was significantly better in the intervention arm (hazardratio,2.6[1.4–4.9];P=0.003)after censoring those with bed aquiline replacement in the SOC arm(and this pattern remained consistent after censoring for drug replacement in both arms ;P=0.01). Conclusions: Compared with traditional injectable-containing regimens, an all-oral 6-month levofloxacin, bed aquiline, and linezolid–containing MDR/RR-TB regimen was associated with a significantly improved 24-month WHO-defined treatment outcome (predominantly owing to toxicity-related drugs substitution).However, drug toxicity occurred frequently in both arms. These findings form strategies to develop future regimens for MDR/RR-TB. Clinical trial registered with www.clinicaltrials.gov (NCT02454205).
Keywords: Drug-resistant tuberculosis; All-oral regimen; Shortened regimen; Bedaquiline; Linezolid; SDG-3: Good health and well-being